PENGGUNAAN STRATEGI PEMBELAJARAN UNTUK MENCIPTAKAN PEMBELAJARAN AKTIF DAN INOVATIF - Achmad Yusuf; Mahmudi Mahmudi (Edupedia : Jurnal Studi Pendidikan dan Pedagogi Islam, 2021)
the effective learning is the learning that can stimulate the enthusiasm and enjoyment of students follow the learning process. However, the obstacle of that, there are no many Islamic religious education teachers who are skilled in preparing and implementing lessons that are able to arouse the enthusiasm of their students and the lack of attention from school principals on the development of PAI learning in schools, including the availability of inadequate facilities and infrastructure. Therefore, teachers must be creative in designing learning activities, one of which is using appropriate learning strategies. The learning strategy that can create active and creative learning is the PAIKEM strategy. PAIKEM is a teaching and learning strategy that contains six important elements, that are learning, active, innovative, creative, effective and fun. The six elements have different characteristics and interpretations and must be integrated by the teacher who will apply them. The supporting factors of PAIKEM implementation include infrastructure, the ability of teachers to implement PAIKEM, and the readiness of students to receive the lessons. The inhibiting factors in implementing PAIKEM include the number of students, time allocation, and schedule changes.